Una geografía de la gentrificación en el centro histórico de Palma (Mallorca, España). Turismo y elitización social - Jesús M. González Pérez (Confins)
Gentrification is a widespread phenomenon that has become a threat for many old quarters. This is the case of the pre-industrial old quarter of Palma (Mallorca), the capital of one of the Mediterranean’s leading tourist destinations. The aim of this paper is to study the process of gentrification in Palma’s old quarter, using four main indicators: demographic (the foreign population), tourist-related (hotels and holiday homes) and economic (income per household and the real estate market). The analysis is conducted on an intra-urban scale (census blocks) in order to detect urban inequalities and spatial patterns in the location and/or distribution of these variables. The study identifies a series of trends: growing internationalization (of the resident population, hotel investment capital, tourists, real estate investors etc.), increased specialization in tourism, the diversification of holiday accommodation, and growing elitism and social uniformity.